Can mediastinum cause referred pain in idiopathic scoliosis? (Annals of Medical Research, 2023)
Aim: In idiopathic scoliosis (IS), the mechanism of action of the pain that occurs, especially in the back and neck region, with the increase in curvature, is not known exactly. In the study, the relationship between these pains and the mediastinum was investigated.Materials and Methods: The study, which was planned retrospectively, included 25 individuals with IS (Lenke Type I) and 21 healthy individuals. Individuals with IS determined the regions where they felt the most pain on the body diagram. The lung and mediastinal volumes of the participants were measured in mm3 on computed tomography (CT) images. The ratios of the area occupied by the lung and mediastinum in the thoracic cavity were calculated in each group. The obtained data were evaluated using the IBM SPSS 23.0 program, and p
Keywords: Scoliosis; Mediastinum; Lung; Referred Pain; Pleura Parietalis